INFERTILITY ASSOCIATED WITH ENDOMETRIOSIS – IS IT A “DILEMMA” OR ALL ABUNDANTLY CLEAR? - M. R. Orazov; V. E. Radzinsky; M. B. Hamoshina; I. N. Kostin; V. N. Lokshin; E. V. Kavteladze; V. B. Shustova; I. F. Puchalskaya (Scientific Journal of Pedagogy and Economics, 2019)
Endometriosis is still a phenomenon that hides its true face and there is nothing surprising in the fact that this pathological condition is a "disease of mysteries and assumptions." "The problem is within the problem" is infertility on the background of endometriosis with radically different ways of its overcoming. The hypothesis that endometriosis causes infertility or reduces fertility remain controversial. The review deals with the pathogenesis, diagnosis and treatment of infertility, associated endometriosis.